DAMPAK PEMBANGUNAN INFRASTRUKTUR PERDESAAN PADA PROGRAM PNPM MANDIRI PERDESAAN DI KABUPATEN TOLI TOLI - Labombang, Mastura (MEKTEK, 2011)
The purpose of this study was to determine the Development Impact of Rural Infrastructure in PNPM RuralProgram in Toli-Toli. Research conducted on the implementation of PNPM Rural Program in Toli-Toli forfiscal year 2007 and 2008.Primary data obtained from interviews with relevant parties and direct observation in the field, then the datais processed with Descriptive Analysis.The results showed the impact of rural infrastructure development in poor communities in Toli Toli, namely:increasing revenue, impoving public education, improving health and improving the public midset. Impact onvillage institutions, namely: the function and role of local government to be effective, institutions ofparticipatory development and improvement of the quality of facilities.and social infrastructure andeconomic base of society